Diffusion‐weighted imaging (DWI) highlights SDHB‐related tumours: A pilot study. (11th April 2019) - Tufton, Nicola; White, Gemma; Drake, William M.; Sahdev, Anju; Akker, Scott A.
Abstract: Objective: There is consensus that asymptomatic carriers of SDHB mutations should undergo periodic surveillance imaging. MRI has the advantage of avoiding radiation exposure but its sensitivity and specificity for detecting phaeochromocytoma and paraganglioma (PPGL) are dependent on sequences performed and expertise of reporting radiologists. We aim to highlight the additional value of diffusion‐weighted imaging (DWI) for MR based surveillance, demonstrating DWI's ability to identify small PPGLs at all body sites. Design: We presented DWI sequences taken as part of SDHB surveillance to a radiologist, expert in reporting PPGL screening scans. Areas of high signal on DWI were interrogated using other standard MRI sequences. Patients: We reviewed the MRI scans for 18 SDHB mutation carriers with a total of 18 histologically proven SDHB‐ related tumours and 12 presumed PGLs/metastatic deposits. Results: The DWI sequences identified all 30 lesions. False‐positive lesions were excluded by standard sequences. The tumours detected by DWI ranged in size from 5 to 52 mm. PPGLs were identified on DWI in the abdomen (n = 14), adrenal gland (n = 1), thorax (n = 3), neck (n = 2) and bladder (n = 2). Additionally, other SDHB ‐related tumours (GIST, RCC) were also highlighted by DWI, as were metastatic deposits in the liver and bone. Conclusions: These preliminary data suggest that DWI has high sensitivity and can identify even small SDHB ‐related tumours. If these findings are confirmed in larger series, for all SDH subunits, it will provide reassurance about identifying small SDH ‐related tumours, without exposing patients to the consequences of radiation‐based imaging and will secure the role of MRI for surveillance imaging.